PENERAPAN BUDIDAYA PADI DENGAN METODE SRI (SISTEM OF RICE INTENSIFICATION) DI DESA PATEMON KECAMATAN BOJONGSARI KABUPATEN PURBALINGGA - Okti Herliana; Sapto Nugroho Hadi; Wilis Cahyani (Dinamika Journal : Pengabdian Masyarakat, 2019)
Patemon Village is located in the District of Bojongsari, Purbalingga Regency, approximately 17 Km from the General Soedirman University Campus with a total of 528 Family Heads and a population of 4350 people. The livelihoods of the population are mostly farmers. Agricultural potential of Patemon Village, Bojongsari Subdistrict includes: rice, corn, soybeans and cassava. The area of paddy fields in this village reaches 128,000 ha but unfortunately its productivity is still relatively low. This is because farmers are still implementing conventional cultivation systems and lack of knowledge about integrated crop management. This activity aims to provide knowledge and examples of alternative rice cultivation methods, namely rice farming using the SRI (System of Rice Intensification) method with the application of straw compost and vegetable pesticides. This activity involved the target audience, namely the "Warakan Tani" farmer group in Patemon Village, Bojongsari District and agricultural instructors in Bojongsari sub-district. The methods used in this activity are: 1. Direct extension activities to farmer groups 2. Direct practice / rice cultivation demonstration plot using SRI (System of Rice Intensification) method or making demonstration plots. The evaluation design is in the form of providing pre-test before the extension activity begins and post-test after the extension activity begins, this is intended to determine the extent of farmers' understanding of the SRI method.